A STRATEGIC ROLE OF BPRS SRAGEN IN ENHANCING REGIONAL INCOME AND SUSTAINABLE FINANCE - Mehilda Rosdaliva; Diah Pramesti; Rosita Mei Damayanti; Endang Martini (EP FEB UNS, 2026)
Sharia Rural Banks (BPRS) as Regionally-Owned Enterprises face the dual challenge of maximizing dividend contributions to Regional Original Revenue (PAD) while maintaining long-term financial sustainability. BPRS Sragen, 80.42% owned by the Sragen Regency Government, presents a strategic case for examining how regional Islamic financial institutions can optimize this dual role. This study aims to: (1) analyze ROI trends of BPRS Sragen from 2009 to 2024 as a measure of regional capital management efficiency; (2) identify internal and external strategic factors through SWOT analysis; (3) evaluate the pentahelix collaboration model involving government, academia, business, community, and media; and (4) assess the implementation of Net-Zero Bank principles as a sustainability commitment. A qualitative descriptive-analytical approach with a single case study strategy was employed. Quantitative secondary data from BPRS Sragen financial reports (2009–2024) were analyzed for ROI trends. Primary qualitative data were collected through semi-structured in-depth interviews with purposively selected informants, triangulated with internal documents and non-participant observation. Qualitative data were analyzed using Miles, Huberman, and Saldaña's interactive model. Findings indicate a consistent positive ROI trend over 16 years with dividend contributions exceeding regional targets. SWOT analysis reveals competitive strengths in local customer loyalty and government support, offset by threats from digital financial competition. Pentahelix collaboration is partially operational, with significant untapped potential in academic and media dimensions. Net-Zero Bank implementation remains nascent but aligns with Maqasid al-Shariah values. The convergence of financial efficiency, strategic planning, multi-stakeholder collaboration, and sustainability commitment positions BPRS Sragen as a replicable model for regional Islamic financial institutions. This integrative framework offers practical policy implications for BPRS governance reform across Indonesian regions, particularly in optimizing PAD contributions without sacrificing long-term sustainability.